In situ detection of a novel lysozyme monoclinic crystal form upon controlled relative humidity variation. Issue 6 (22nd November 2018) - Trampari, S.; Valmas, A.; Logotheti, S.; Saslis, S.; Fili, S.; Spiliopoulou, M.; Beckers, D.; Degen, T.; Nénert, G.; Fitch, A. N.; Calamiotou, M.; Karavassili, F.; et al.
Abstract : Effects of relative humidity on a novel monoclinic crystal form of hen egg‐white lysozyme are assessed via in situ laboratory X‐ray powder diffraction. Abstract : The effect of relative humidity (rH) on protein crystal structures, an area that has attracted high scientific interest during the past decade, is investigated in this study on hen egg‐white lysozyme (HEWL) polycrystalline precipitates via in situ laboratory X‐ray powder diffraction (XRPD) measurements. For this purpose, HEWL was crystallized at room temperature and pH 4.5, leading to a novel monoclinic HEWL phase which, to our knowledge, has not been reported before. Analysis of XRPD data collected upon rH variation revealed several structural modifications. These observations, on a well‐studied molecule like HEWL, underline not only the high impact of humidity levels on biological crystal structures, but also the significance of in‐house XRPD as an analytical tool in industrial drug development and its potential to provide information for enhancing manufacturing of pharmaceuticals.